A systematic review of the evaluation of agricultural policies: Using prisma - Lina M. Bastidas-Orrego; Natalia Jaramillo; Julián A. Castillo-Grisales; Yony F. Ceballos (Heliyon, 2023)
Background: The food security of each country depends on agricultural development, which is sensitive to the implementation of agricultural public policies. These must evolve as new ruralities arise, with new phenomena, such as climate change, ecosystem services, changes in consumer preferences, globalization, sustainability and ecological awareness. Hence, of ex-ante and ex-post evaluations of agricultural policies, are important because they provide timely information to government entities. There are different methodologies for policy evaluation, which have evolved over time. Aims: This systematic review aims to identify manuscript that systematically review methodologies, policies and variables evaluated during the last 50 years to determine whether a policy has been efficient. To assess the quality of the included manuscript and to describe the measures and domains identified. Methods: EBSCO, Dialnet, SciELO, Scopus, Science Direct, Dimensions and Web of Science were searched. A total of 154 manuscript were identified, the review was finalized by reviewing the title, and abstract and the review was finalized by reviewing the title, abstract and full text, resolving disagreements. Of these 154 manuscripts, 37 met the criteria and were included in the analysis. PRISMA checklists were used to evaluate the methodology. Outcomes and results: It were found that there are few studies on the design of evaluation methodologies for agricultural policies in the literature. Research shows that the latest policy evaluation proposals present more complex methodologies involving tools such as machine learning and agent-based modelling (ABM). On the other hand, the issue of sustainability as a policy is seen in the agri-environmental policy evaluation. Conclusions and implications: The evolution of agricultural policy methodologies can be observed at the beginning with the use of quantitative methodologies, such as matrices, statistics and econometrics. With the emergence of new variables, such as agri-environmental variables, citizen participation and market opening, methodologies have become more comprehensive, combining qualitative and quantitative variables. Methodologies were identified that evaluate robust agricultural policies and others that focus on the evaluation of one or two policies. These studies are important for research that focuses not only on the evaluation of agricultural policies but also on their design and implementation processes.